Antistatic epoxy resin composite coating and preparation method thereof
By combining the surface modification of graphene and physical co -mixing with epoxy resin to prepare a composite coatings of anticiditive epoxy resin, the problem of insufficient anti -static performance and mechanical strength of epoxy resin coatings, which significantly improves the coatings. Anti -static performance and mechanical strength.
Patent Information
- Application Number
- CN202411761372.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-12-03
AI Technical Summary
The existing epoxy resin coatings have shortcomings in antistatic properties and mechanical strength, which are difficult to meet the needs of modern electronic equipment to improve antistatic properties.
By the surface modification of graphene, the ethylene graphene is obtained, and polymerization reactions are performed through an emulsifier and a leading agent to form polyacrylate graphene. Composite coatings of oxygen resin.
It significantly improves the anti -static performance and mechanical strength of epoxy resin coatings. The conductivity of graphene and the enhanced effect of polyacrylate together improve the electrical and antiproference capacity of the coatings.
Smart Images

Figure CN119371875A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, in particular to an antistatic epoxy resin composite coating and a preparation method thereof. Background Art
[0002] With the development of miniaturization of electronic devices and high integration of circuits, the power density of electronic devices is gradually increasing, and the electrostatic sensitivity of their electronic components is also increasing. The application of various epoxy resin materials in the manufacturing process and application of electronic components makes the generation of electrostatic charge easier and more extensive. With the increase of static charge accumulated on the surface of the material, it may cause many hazards to electronic components, such as capturing dust, causing electric field interference, leading to electrostatic discharge accompanied by sparks and a lot of heat, thereby reducing material performance and even damaging sealed circuits. Therefore, improving the antistatic performance of components is extremely important to ensure the safe and reliable operation of electronic components.
[0003] Epoxy resin is often used for packaging of electronic devices due to its excellent processability. However, its inherent insulation makes it unable to meet the growing antistatic demand of modern electronic devices. As a conventional technology to prevent static charge accumulation in epoxy resin matrix materials, an antistatic agent is usually mixed into epoxy resin or an antistatic agent is applied on the surface of epoxy resin. Among them, Chinese Patent Publication No. CN106010118A discloses an epoxy resin coating with antistatic properties and a preparation method thereof, and Chinese Patent Publication No. CN106010141B discloses a preparation method of a uniform antistatic coating. Although both increase the antistatic agent by adding a pure phase, The antistatic properties of epoxy resin coatings have been improved, but they still have the problems of low antistatic properties and high addition amount. To this end, the use of more efficient antistatic agents has become one of the important directions for improving epoxy resin coatings. Among them, various nanoparticles with high conductivity have been used as fillers to improve the antistatic properties of epoxy resin-based composites, such as carbon nanotubes, graphene, etc. Graphene has received much attention in the field of antistatic materials due to its extraordinary electrical properties. In addition, quaternary ammonium salts are also one of the commonly used antistatic agents, but they have poor compatibility with coating matrix materials and are easily precipitated onto the coating surface during use, thereby losing and reducing the antistatic effect of the coating. Grafting them on the graphene surface can avoid such problems.
[0004] 1. Technical issues to be resolved
[0005] In view of the deficiencies in the prior art, the present invention provides an antistatic epoxy resin composite coating and a preparation method thereof, which solves the problems of poor antistatic ability and low mechanical strength of epoxy resin coatings.
[0006] (II) Technical solution
[0007] To achieve the above object, the present invention provides the following technical solution: an antistatic epoxy resin composite coating, the preparation method of the antistatic epoxy resin composite coating comprises the following steps: (1) According to the mass ratio of 10:4500-8000:18-40:80-200, graphene oxide is ultrasonically dispersed in N,N-dimethylformamide, and then γ-methacryloxypropyltrimethoxysilane and ethanol solvent are added, the pH is adjusted to 3-6 hours, and the reaction is carried out at 50-80°C for 8-20 hours. After the reaction is completed, vinyl graphene is obtained; (2) dissolving vinyl graphene and emulsifier OP-10 in deionized water and stirring, then adding butyl acrylate, ethyl acrylate, glycidyl acrylate, acrylic acid and initiator ammonium persulfate (APS), stirring evenly, and reacting. After the reaction is completed, polyacrylate-grafted graphene is obtained; (3) placing polyacrylate grafted graphene, epichlorohydrin, and catalyst triphenylphosphine (PPh3) in a reaction bottle, stirring evenly, and reacting. After the reaction is completed, chlorinated polyacrylate grafted graphene is obtained; (4) stirring the chlorinated polyacrylate grafted graphene and N,N-dimethylethylenediamine, and reacting them to obtain quaternized polyacrylate grafted graphene; (5) The epoxy resin and the quaternary ammonium polyacrylate grafted graphene are ultrasonically dispersed in deionized water, and dispersed evenly under high-speed shear force, and then sand-milled. Then, a defoaming agent polyether-modified silicone and a leveling agent hydroxypropyl methylcellulose are added, and the mixture is stirred evenly. Then, an epoxy curing agent is added thereto, and the mixture is stirred evenly and allowed to stand to obtain an antistatic epoxy resin composite coating.
[0008] Preferably, in step (2), the mass ratio of vinyl graphene, emulsifier OP-10, deionized water, butyl acrylate, ethyl acrylate, glycidyl acrylate, acrylic acid and ammonium persulfate is 100:350-800:1600-3000:30-60:30-60:15-30:35-80:7-15.
[0009] Preferably, in step (2), the reaction temperature is 60-90° C. and the reaction time is 4-10 h.
[0010] Preferably, in step (3), the mass ratio of polyacrylate grafted graphene, epichlorohydrin and triphenylphosphine is 100:45-80:0.3-0.8.
[0011] Preferably, in step (3), the reaction temperature is 80-120° C. and the reaction time is 8-20 h.
[0012] Preferably, in step (4), the mass ratio between the chlorinated polyacrylate grafted graphene and N,N-dimethylethylenediamine is 100:35-90.
[0013] Preferably, in step (4), the reaction temperature is 50-90° C. and the reaction time is 5-12 h.
[0014] Preferably, the type of curing agent in step (5) includes tetrahydromethylphthalic anhydride or hexahydrophthalic anhydride.
[0015] Preferably, in step (5), the mass ratio of epoxy resin, quaternized polyacrylate grafted graphene, deionized water, polyether modified silicone, hydroxypropyl methylcellulose and epoxy curing agent is 100:2-6:20-40:0.5-1:0.35-0.8:25-60.
[0016] 3. Beneficial technical effects
[0017] Compared with the prior art, the present invention has the following experimental principles and beneficial technical effects: The invention discloses an antistatic epoxy resin composite coating. Firstly, γ-methacryloxypropyltrimethoxysilane is used to modify the surface of graphene oxide to obtain vinyl graphene. Then, an emulsifier OP-10 is used to emulsify the solution. Ammonium persulfate is used as an initiator to carry out in-situ polymerization reaction between the alkenyl group of vinyl graphene and butyl acrylate, ethyl acrylate, glycidyl acrylate and acrylic acid to obtain polyacrylate grafted graphene. Then, triphenylphosphine is used as a catalyst to cause a ring-opening reaction between the carboxyl group in the polyacrylate grafted graphene and the epoxy group of epichlorohydrin to obtain chlorinated polyacrylate grafted graphene. Then, the chlorinated polyacrylate grafted graphene is subjected to a quaternization reaction with N,N-dimethylethylenediamine to obtain quaternized polyacrylate grafted graphene. Finally, the antistatic epoxy resin composite coating is prepared by physical blending.
[0018] The antistatic epoxy resin composite coating has better antistatic effect and mechanical strength than pure epoxy resin coating. Graphene, as an excellent conductive material, is added to the epoxy resin matrix coating to form a network structure with good conductivity with the epoxy resin matrix material, thereby increasing the conductivity of the coating. 2Hybrid structure, the obstacles encountered by electrons in the coating during transmission are reduced, so that they can move freely in the lattice. In addition, when the coating is subjected to external force, with the help of the graphene-epoxy resin network structure, the stress can be dispersed as much as possible in the entire coating structure, avoiding the damage caused by stress concentration, thereby increasing the mechanical strength of the epoxy resin coating. Adding quaternary ammonium salts to the coating can further reduce the resistivity of the epoxy resin coating and increase its antistatic effect. The quaternary ammonium salt contains a large number of carbon chain and polar ion functional group structures, among which the carbon chain structure can be intertwined with the epoxy resin structure to achieve the purpose of capacity increase, and the polar functional group has good hydrophilicity. By absorbing water molecules on the surface of the substrate, a conductive film structure is formed, which further increases the coating structure. Conductivity reduces resistance. Grafting quaternary ammonium salts on the surface of graphene can not only promote the synergistic effect between the two and increase the antistatic effect of the coating, but also avoid the precipitation of quaternary ammonium salts in the matrix, increasing the stability of the antistatic coating. The amino group of the quaternary ammonium salt can also act as an amine promoter, and at the same time act on epoxy resins and acid anhydride curing agents, reducing the reaction activity of the curing agent, improving the performance of the cured product, and reducing the harm of the acid curing agent, promoting the curing behavior of the epoxy resin, and adding polyacrylates to epoxy resin coatings can improve the mechanical strength of the coating. When polyacrylates are added to the coating, the coating will be affected by external forces and silver streaks will appear. The silver streaks will absorb a large amount of destructive energy during the appearance and development of fractures, thereby increasing the mechanical strength of the epoxy resin coating. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 is a schematic diagram of the structure of polyacrylate grafted graphene; Figure 2 It is the reaction formula of polyacrylate grafted graphene and epichlorohydrin; Figure 3 It is the reaction formula of chlorinated polyacrylate grafted graphene and N,N-dimethylethylenediamine. DETAILED DESCRIPTION
[0020] To achieve the above object, the present invention provides the following specific implementation methods and embodiments: An antistatic epoxy resin composite coating, the preparation method of which comprises the following steps: (1) According to the mass ratio of 10:4500-8000:18-40:80-200, graphene oxide is ultrasonically dispersed in N,N-dimethylformamide, and then γ-methacryloxypropyltrimethoxysilane and ethanol solvent are added, the pH is adjusted to 3-6 hours, and the reaction is carried out at 50-80°C for 8-20 hours. After the reaction is completed, it is filtered and washed with ethanol for 2-4 times, and then the vinyl graphene is completely obtained at 40-60°C; (2) dissolving vinyl graphene and emulsifier OP-10 in deionized water in a mass ratio of 100:350-800:1600-3000:30-60:30-60:15-30:35-80:7-15, and stirring, then adding butyl acrylate, ethyl acrylate, glycidyl acrylate, acrylic acid and initiator ammonium persulfate (APS), stirring evenly, reacting at 60-90°C for 4-10h, and after the reaction is completed, centrifuging at a speed of 4000-6000r / min, washing, and obtaining polyacrylate grafted graphene; (3) placing polyacrylate grafted graphene, epichlorohydrin, and catalyst triphenylphosphine (PPh3) in a reaction bottle at a mass ratio of 100:45-80:0.3-0.8, stirring evenly, reacting at 80-120°C for 8-20h, filtering after the reaction, and washing with ethanol to obtain chlorinated polyacrylate grafted graphene; (4) Chlorinated polyacrylate grafted graphene and N,N-dimethylethylenediamine are mixed in a mass ratio of 100:35-90, stirred evenly, reacted at 50-90° C. for 5-12 hours, filtered, and washed with ethanol to obtain quaternized polyacrylate grafted graphene; (5) According to the mass ratio of 100:2-6:20-40:0.5-1:0.35-0.8:25-60, the epoxy resin and the quaternized polyacrylate grafted graphene are ultrasonically dispersed in deionized water, and dispersed evenly under high-speed shear force, and then sand-milled, and then a defoaming agent polyether-modified silicone and a leveling agent hydroxypropyl methylcellulose are added, stirred evenly, and then an epoxy curing agent is added thereto, wherein the type of curing agent includes tetrahydromethylphthalic anhydride or hexahydrophthalic anhydride, stirred evenly, and allowed to stand to obtain an antistatic epoxy resin composite coating.
[0021] Example 1 (1) Ultrasonic dispersion of 5 g of graphene oxide in 2500 g of N,N-dimethylformamide, then adding 9 g of γ-methacryloxypropyltrimethoxysilane and 40 g of ethanol solvent, adjusting the pH to 3 h, reacting at 50 ° C for 8 h, filtering after the reaction, washing with ethanol twice, and cooling at 40 ° C until vinyl graphene is completely obtained; (2) Dissolve 5 g of vinyl graphene and 17.5 g of emulsifier OP-10 in 80 g of deionized water and stir, then add 1.5 g of butyl acrylate, 1.5 g of ethyl acrylate, 0.75 g of glycidyl acrylate, 1.75 g of acrylic acid and 0.35 g of initiator ammonium persulfate (APS), stir evenly, react at 60 ° C for 4 h, after the reaction is completed, centrifuge at a speed of 4000 r / min, wash, and obtain polyacrylate grafted graphene; (3) 4 g polyacrylate grafted graphene, 1.8 g epichlorohydrin, and 0.012 g catalyst triphenylphosphine (PPh3) were placed in a reaction bottle, stirred evenly, and reacted at 80 °C for 8 h. After the reaction was completed, the mixture was filtered and washed with ethanol to obtain chlorinated polyacrylate grafted graphene; (4) 4 g of chlorinated polyacrylate grafted graphene and 1.4 g of N,N-dimethylethylenediamine were stirred evenly, reacted at 50 °C for 5 h, filtered, and washed with ethanol to obtain quaternary ammonium polyacrylate grafted graphene; (5) 10 g of epoxy resin and 0.2 g of quaternized polyacrylate grafted graphene are ultrasonically dispersed in 2 g of deionized water, and dispersed evenly under high-speed shear force, and then sand-milled. Then, 0.05 g of defoaming agent polyether-modified silicone and 0.035 g of leveling agent hydroxypropyl methylcellulose are added and stirred evenly. Then, 2.5 g of epoxy curing agent is added thereto, wherein the type of curing agent includes tetrahydromethylphthalic anhydride or hexahydrophthalic anhydride. After stirring evenly, the mixture is allowed to stand to obtain an antistatic epoxy resin composite coating.
[0022] Example 2 (1) Ultrasonic dispersion of 5 g of graphene oxide in 3000 g of N,N-dimethylformamide, then adding 10 g of γ-methacryloxypropyltrimethoxysilane and 60 g of ethanol solvent, adjusting the pH to 4 h, reacting at 60 ° C for 10 h, filtering after the reaction, washing with ethanol twice, and heating at 45 ° C until vinyl graphene is completely obtained; (2) Dissolve 5 g of vinyl graphene and 20 g of emulsifier OP-10 in 100 g of deionized water and stir, then add 2 g of butyl acrylate, 2 g of ethyl acrylate, 1 g of glycidyl acrylate, 2 g of acrylic acid and 0.4 g of initiator ammonium persulfate (APS), stir evenly, react at 70 ° C for 5 h, and after the reaction is completed, centrifuge at a speed of 4500 r / min and wash to obtain polyacrylate grafted graphene; (3) 4 g of polyacrylate-grafted graphene, 2.4 g of epichlorohydrin, and 0.016 g of catalyst triphenylphosphine (PPh3) were placed in a reaction bottle, stirred evenly, and reacted at 90 °C for 10 h. After the reaction was completed, the mixture was filtered and washed with ethanol to obtain chlorinated polyacrylate-grafted graphene; (4) 4 g of chlorinated polyacrylate grafted graphene and 2 g of N,N-dimethylethylenediamine were stirred evenly, reacted at 60 °C for 6 h, filtered, and washed with ethanol to obtain quaternized polyacrylate grafted graphene; (5) 10 g of epoxy resin and 0.3 g of quaternized polyacrylate grafted graphene are ultrasonically dispersed in 2.5 g of deionized water, and dispersed evenly under high-speed shear force, and then sand-milled. Then, 0.06 g of defoaming agent polyether-modified silicone and 0.04 g of leveling agent hydroxypropyl methylcellulose are added and stirred evenly. Then, 3 g of epoxy curing agent is added thereto, wherein the type of curing agent includes tetrahydromethylphthalic anhydride or hexahydrophthalic anhydride. After stirring evenly, the mixture is allowed to stand to obtain an antistatic epoxy resin composite coating. Example 3
[0023] (1) Ultrasonic dispersion of 5 g of graphene oxide in 3500 g of N,N-dimethylformamide, then adding 16 g of γ-methacryloxypropyltrimethoxysilane and 80 g of ethanol solvent, adjusting the pH to 5 h, reacting at 70 ° C for 16 h, filtering after the reaction, washing with ethanol 3 times, and heating at 50 ° C until vinyl graphene is completely obtained; (2) Dissolve 5 g of vinyl graphene and 30 g of emulsifier OP-10 in 120 g of deionized water and stir, then add 2.5 g of butyl acrylate, 2.5 g of ethyl acrylate, 1.2 g of glycidyl acrylate, 3 g of acrylic acid and 0.6 g of initiator ammonium persulfate (APS), stir evenly, react at 80 ° C for 8 h, after the reaction is completed, centrifuge at a speed of 5000 r / min, wash, and obtain polyacrylate grafted graphene; (3) 4 g of polyacrylate-grafted graphene, 2.8 g of epichlorohydrin, and 0.028 g of catalyst triphenylphosphine (PPh3) were placed in a reaction bottle, stirred evenly, and reacted at 100 °C for 16 h. After the reaction was completed, the mixture was filtered and washed with ethanol to obtain chlorinated polyacrylate-grafted graphene; (4) 4 g of chlorinated polyacrylate grafted graphene and 3.2 g of N,N-dimethylethylenediamine were stirred evenly, reacted at 80 °C for 10 h, filtered, and washed with ethanol to obtain quaternized polyacrylate grafted graphene; (5) 10 g of epoxy resin and 0.5 g of quaternized polyacrylate grafted graphene are ultrasonically dispersed in 3.5 g of deionized water, and dispersed evenly under high-speed shear force, and then sand-milled. Then, 0.08 g of defoaming agent polyether-modified silicone and 0.06 g of leveling agent hydroxypropyl methylcellulose are added and stirred evenly. Then, 5 g of epoxy curing agent is added thereto, wherein the type of curing agent includes tetrahydromethylphthalic anhydride or hexahydrophthalic anhydride. After stirring evenly, the mixture is allowed to stand to obtain an antistatic epoxy resin composite coating. Example 4
[0024] (1) 5 g of graphene oxide was ultrasonically dispersed in 4000 g of N,N-dimethylformamide, and then 20 g of γ-methacryloxypropyltrimethoxysilane and 100 g of ethanol solvent were added. After adjusting the pH to 6 h, the mixture was reacted at 80 ° C for 20 h. After the reaction was completed, the mixture was filtered and washed with ethanol for 4 times, and then cooled at 60 ° C until the vinyl graphene was completely obtained. (2) Dissolve 5 g of vinyl graphene and 40 g of emulsifier OP-10 in 150 g of deionized water and stir, then add 3 g of butyl acrylate, 3 g of ethyl acrylate, 1.5 g of glycidyl acrylate, 4 g of acrylic acid and 0.75 g of initiator ammonium persulfate (APS), stir evenly, react at 90 ° C for 10 h, and after the reaction is completed, centrifuge at a speed of 6000 r / min and wash to obtain polyacrylate grafted graphene; (3) 4 g of polyacrylate grafted graphene, 3.2 g of epichlorohydrin, and 0.032 g of catalyst triphenylphosphine (PPh3) were placed in a reaction bottle, stirred evenly, and reacted at 120 °C for 20 h. After the reaction was completed, the mixture was filtered and washed with ethanol to obtain chlorinated polyacrylate grafted graphene; (4) 4 g of chlorinated polyacrylate grafted graphene and 3.6 g of N,N-dimethylethylenediamine were stirred evenly, reacted at 90 °C for 12 h, filtered, and washed with ethanol to obtain quaternized polyacrylate grafted graphene; (5) 10 g of epoxy resin and 0.6 g of quaternized polyacrylate grafted graphene are ultrasonically dispersed in 4 g of deionized water, and dispersed evenly under high-speed shear force, and then sand-milled. Then, 0.1 g of defoaming agent polyether-modified silicone and 0.08 g of leveling agent hydroxypropyl methylcellulose are added and stirred evenly. Then, 6 g of epoxy curing agent is added thereto, wherein the type of curing agent includes tetrahydromethylphthalic anhydride or hexahydrophthalic anhydride. After stirring evenly, the mixture is allowed to stand to obtain an antistatic epoxy resin composite coating.
[0025] Comparative Example 1 (1) Ultrasonic dispersion of 5 g of graphene oxide in 3000 g of N,N-dimethylformamide, then adding 10 g of γ-methacryloxypropyltrimethoxysilane and 60 g of ethanol solvent, adjusting the pH to 4 h, reacting at 60 ° C for 10 h, filtering after the reaction, washing with ethanol 3 times, and heating at 40 ° C until vinyl graphene is completely obtained; (2) Dissolve 5 g of vinyl graphene and 20 g of emulsifier OP-10 in 120 g of deionized water and stir, then add 2.4 g of butyl acrylate, 2.4 g of ethyl acrylate, 1.2 g of glycidyl acrylate, 2 g of acrylic acid and 0.4 g of initiator ammonium persulfate (APS), stir evenly, react at 80 ° C for 8 h, after the reaction is completed, centrifuge at a speed of 4500 r / min, wash, and obtain polyacrylate grafted graphene; (3) 10 g of epoxy resin and 0.3 g of polyacrylate grafted graphene are ultrasonically dispersed in 3 g of deionized water, and dispersed evenly under high-speed shear force, and then sand-milled. Then, 0.08 g of defoaming agent polyether-modified silicone and 0.06 g of leveling agent hydroxypropyl methylcellulose are added and stirred evenly. Then, 4 g of epoxy curing agent is added thereto, wherein the types of curing agents include tetrahydromethylphthalic anhydride or hexahydrophthalic anhydride. After stirring evenly, the mixture is allowed to stand to obtain an antistatic epoxy resin composite coating.
[0026] Comparative Example 2 (1) 10 g of epoxy resin and 0.3 g of graphene are ultrasonically dispersed in 2 g of deionized water, and dispersed evenly under high-speed shear force, and then sand-milled. Then, 0.08 g of defoaming agent polyether-modified silicone and 0.07 g of leveling agent hydroxypropyl methylcellulose are added and stirred evenly. Then, 4 g of epoxy curing agent is added thereto, wherein the type of curing agent includes tetrahydromethylphthalic anhydride or hexahydrophthalic anhydride. After stirring evenly, the mixture is allowed to stand to obtain an antistatic epoxy resin composite coating.
[0027] The resistivity test of antistatic epoxy resin composite coating was carried out according to the national standard GB / T 11210-2014.
[0028] test Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Resistivity (Ω) <![CDATA[1.70×10 9 ]]> <![CDATA[2.71×10 6 ]]> <![CDATA[6.28×10 5 ]]> <![CDATA[7.67×10 8 ]]> <![CDATA[3.15×10 12 ]]> <![CDATA[8.08×10 12 ]]> The mechanical strength test of antistatic epoxy resin composite coating was carried out according to the national standard GB / T 1732-1979 (88).
[0029]
Claims
1. An antistatic epoxy resin composite coating, characterized in that: The preparation method of the antistatic epoxy resin composite coating comprises the following steps: (1) According to the mass ratio of 10:4500-8000:18-40:80-200, graphene oxide is ultrasonically dispersed in N,N-dimethylformamide, and then γ-methacryloxypropyltrimethoxysilane and ethanol solvent are added, the pH is adjusted to 3-6 hours, and the reaction is carried out at 50-80°C for 8-20 hours. After the reaction is completed, vinyl graphene is obtained; (2) dissolving vinyl graphene and emulsifier OP-10 in deionized water and stirring, then adding butyl acrylate, ethyl acrylate, glycidyl acrylate, acrylic acid and initiator ammonium persulfate (APS), stirring evenly, and reacting. After the reaction is completed, polyacrylate-grafted graphene is obtained; (3) placing polyacrylate grafted graphene, epichlorohydrin, and catalyst triphenylphosphine (PPh3) in a reaction bottle, stirring evenly, and reacting. After the reaction is completed, chlorinated polyacrylate grafted graphene is obtained; (4) stirring the chlorinated polyacrylate grafted graphene and N,N-dimethylethylenediamine, and reacting them to obtain quaternized polyacrylate grafted graphene; (5) The epoxy resin and the quaternary ammonium polyacrylate grafted graphene are ultrasonically dispersed in deionized water, and dispersed evenly under high-speed shear force, and then sand-milled. Then, a defoaming agent polyether-modified silicone and a leveling agent hydroxypropyl methylcellulose are added, and the mixture is stirred evenly. Then, an epoxy curing agent is added thereto, and the mixture is stirred evenly and allowed to stand to obtain an antistatic epoxy resin composite coating.
2. The antistatic epoxy resin composite coating according to claim 1, characterized in that: In the step (2), the mass ratio of vinyl graphene, emulsifier OP-10, deionized water, butyl acrylate, ethyl acrylate, glycidyl acrylate, acrylic acid and ammonium persulfate is 100:350-800:1600-3000:30-60:30-60:15-30:35-80:7-15.
3. The antistatic epoxy resin composite coating according to claim 1, characterized in that: In the step (2), the reaction temperature is 60-90° C. and the reaction time is 4-10 h.
4. The antistatic epoxy resin composite coating according to claim 1, characterized in that: In the step (3), the mass ratio of polyacrylate grafted graphene, epichlorohydrin and triphenylphosphine is 100:45-80:0.3-0.
8.
5. The antistatic epoxy resin composite coating according to claim 1, characterized in that: In the step (3), the reaction temperature is 80-120° C. and the reaction time is 8-20 h.
6. The antistatic epoxy resin composite coating according to claim 1, characterized in that: In the step (4), the mass ratio between the chlorinated polyacrylate grafted graphene and N,N-dimethylethylenediamine is 100:35-90.
7. The antistatic epoxy resin composite coating according to claim 1, characterized in that: In the step (4), the reaction temperature is 50-90° C. and the reaction time is 5-12 h.
8. The antistatic epoxy resin composite coating according to claim 1, characterized in that: The type of curing agent in step (5) includes tetrahydromethylphthalic anhydride or hexahydrophthalic anhydride.
9. The antistatic epoxy resin composite coating according to claim 1, characterized in that: In the step (5), the mass ratio of epoxy resin, quaternized polyacrylate grafted graphene, deionized water, polyether modified silicone, hydroxypropyl methylcellulose and epoxy curing agent is 100:2-6:20-40:0.5-1:0.35-0.8:25-60.
Citation Information
Patent Citations
Epoxy resin paint with antistatic property and preparation method thereof
CN106010118A
Preparation method of a uniform antistatic coating
CN106010141B
PVC (Polyvinyl Chloride) / graphite alkene antistatic composite material and preparation method thereof
CN102775700A
Modified graphene oxide acrylic resin as well as preparation method and application thereof
CN113754825A
Anti-static graphene coating and application method thereof
CN114891418A
Cited By
Antistatic polyester fiber for clothing and preparation method thereof
CN121874960A
An antistatic polyester fiber for clothing and accessories and its preparation method
CN121874960B